LEARNING ENVIRONMENT OF MADRASAH EDUCATION IN THE ASIA’S LATIN CITY - Sheeva M. Yahcob-Saddalani, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The madrasah education is good in both the physical plant and facilities and the teaching and learning resources but only according to the minority views. This implies the existence of some problems in these identified areas of concern of madrasah education in Zamboanga City, Philippines. Thus, there is a need to address these issues of the physical plant and facilities and the teaching and learning resourcesfor more effective religious education in that culturally diverse community, commonly known as the Asia’s Latin City.